Development of a new quantitative RT-PCR to detect lymphocytic choriomeningitis virus - Herrero, Laura; Labiod, Nuria; Molero, Francisca; Potente, Arantxa; Sánchez-Seco, María Paz; Vázquez, Ana (Frontiers in Veterinary Science, 2025)
Lymphocytic choriomeningitis virus (LCMV) is a neglected rodent-borne virus, with a worldwide distribution. The common mouse Mus musculus acts as reservoir and vector in the biological cycle of the virus. Surveillance of LCMV infection in mice is of importance as they are a widely used animal model in research and, through contact with them or their fluids, humans can be infected. Although most human cases are asymptomatic, LCMV infection can cause mild to severe, even fatal, and new diagnostic tools need to be developed to improve its detection. In the present work we report the development of a new method for the detection of LCMV RNA by quantitative reverse transcription polymerase chain reaction (RT-qPCR), able to detect all LCMV strains described to date. RT-qPCR targeting the S segment was developed and evaluated. Specificity and sensitivity were determined, and its limit of detection (LOD) was defined. The method designed is able to detect all 5 LCMV lineages described to date, with a LOD of 5.6 genome copies/μL. Its design with a built-in internal amplification control allows the detection of false negative results. Other arenaviruses were found not to cross-react with the method designed. In conclusion, a new diagnostic RT-qPCR for the detection of LCMV have successfully designed and validated. Improved detection techniques allow to reduce the turnaround time in the diagnosis of infections and to improve epidemiological surveillance in humans and animals.